Peran Aktivitas Fisik terhadap Massa Otot Pasien Diabetes Melitus Tipe 2: Systematic Literatur Riview - Cahyani Sri Afriliya Salim; Riry Ambarsarie; Ety Febrianti (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Diabetes mellitus (DM) is a metabolic disorder resulting from a defect insulin secretion, insulin action, or both. It is one of the chronic noncommunicable diseases which have emerged global health problem and predicted the number raise to 628,6 million by 2045. Type 2 diabetes mellitus related with muscle mass decreased from increased of ubiquitin-proteasome pathway,autophagi-lisosome and caspase-3-mediated proteolytic that have roles in muscle protein degradation. Physical activity showed positive correlation with oxidative capasity repair in skeletal muscle. Physical activity effect increase muscle protein synthesis that inhibite muscle mass decrease. Physical activity is variety of movements resulting from skeletal muscle movement to produce energy, increase ability of muscle, muscle repair, cardiorespiratory, bone health, and reduce the risk of depression and non-communicable diseases. Physical activity level divided into 3 group; light physical activity (intensity <3 MET), moderate activity (intensty 3-5,9 MET), and vigerous activity (intensity ≥6 MET). This review aims to exploration the role of physical activity level to muscle mass in type 2 diabetes mellitus. We collected primer data from various references from 2010-2020 from PubMed and Cochrane database. The references collected is characteristic of physical activit and muscle mass in type 2 diabetes mellitus, effect of physical activity tomuscle mass and insullin sensitivity and inflammation in type 2 diabetes mellitus. This review is a systematic literature review used Cook and West's concepts.